The influence of the big five personality traits in team selection for construction project - Chong, Yew Puay (2015)
This research was conducted to find out the influence of Big Five Personality Traits in team selection for construction project in Petaling Jaya, Selangor area. There are five personality traits studies in this research which are openness, extraversion, conscientiousness, neuroticism and agreeableness. Two sections of questionnaires were developed and distributed to construction managers and their subordinates respectively. A total sample of 82 respondents was used in this study. The results of this study showed that all five personality traits are significant with the team selection for construction project. Besides that, the openness presented the high impact to influence team selection for construction project. The neuroticism‟s opposite is emotional stability that also using in this study to show better understanding. Openness testing can be a guideline to human resources team to select the best construction team to accomplish the project more efficiency.